Quota Formula Review : Data Update and Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
At the conclusion of the 14th General Review of Quotas (14th Review), the Board of Governors requested that a comprehensive review of the quota formula be completed by the Executive Board by January 2013. The timetable for completing the 15th General Review was also brought forward by two years to January 2014. This paper is intended to serve as background for an initial informal exchange of views on issues relating to the formula review. It begins with a brief stock-take, before presenting the results of updating the quota database through 2009. The remainder of the paper discusses potential issues that could be considered as part of the review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet